Assessment Of Some Biochemical Markers Of Bone Turnover In Thyroid Dysfunction State. - A. Y. MANE; V. R. BHAGWAT (International Journal of Pharma and Bio Sciences, 2012)
Thyroid hormones affect bone metabolism by altering normal bone remodeling processes. This study involved assessment of biochemical markers of bone turnover in 94 patients with thyroid dysfunction. Clear hypocalcaemia was observed in hypothyroidism while in hyperthyroid patients there was frank hypercalcaemia. In hyperthyroidism there is increased activity of osteoclast which leads to increased bone turnover (increased resorption/demineralization). Serum magnesium levels were lower in hypothyroid patients, which is the result of impaired magnesium homeostasis. Serum alkaline phosphatase levels were highest in hyperthyroid patients. The biochemical profile of elevated bone specific alkaline phosphatase, total calcium and ionised calcium together with normal liver function tests strongly indicate that bone resorption occurs at higher rate and speeded up by the thyroid hormones in hyperthyroid patients. Bone turnover is increased in favor of resorption and the rate is associated with the levels of thyroid hormones in hyperthyroidism. Opposite changes occur in hypothyroid patient. If other reasons for increased bone turnover are ruled out then elevated bone resorption markers point to subclinical hyperthyroidism.